2009
DOI: 10.1159/000167017
|View full text |Cite
|
Sign up to set email alerts
|

Cardiac Disease in the Dialysis Patient: Good, Better, Best Clinical Practice

Abstract: Proven strategies to reduce cardiovascular events and cardiac mortality in hemodialysis patients are given on the basis of pathophysiology. This is an overview of our clinical know-how acquired during the last 30 years. We try to answer the following questions: (1) how to reduce cardiovascular events and cardiac mortality in hemodialysis patients; (2) how to achieve regression of left ventricular hypertrophy, the most important predictor of sudden cardiac death; (3) how to manage iron status during full correc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0
2

Year Published

2010
2010
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 58 publications
0
6
0
2
Order By: Relevance
“…LV dilatation and systolic and diastolic dysfunction are common and independently associated with mortality [3,4]. These changes are postulated to result from chronic volume overload (due to salt and water retention, chronic anaemia and arteriovenous fistulae), pressure overload (due to hypertension, atherosclerosis, vascular and cardiac valvular calcification), metabolic (acidosis, malnutrition, inflammation and oxidative stress) and neuroendocrine (renin-angiotensin-aldosterone and sympathetic activation) factors and ischaemia [5,6].…”
Section: Discussionmentioning
confidence: 99%
“…LV dilatation and systolic and diastolic dysfunction are common and independently associated with mortality [3,4]. These changes are postulated to result from chronic volume overload (due to salt and water retention, chronic anaemia and arteriovenous fistulae), pressure overload (due to hypertension, atherosclerosis, vascular and cardiac valvular calcification), metabolic (acidosis, malnutrition, inflammation and oxidative stress) and neuroendocrine (renin-angiotensin-aldosterone and sympathetic activation) factors and ischaemia [5,6].…”
Section: Discussionmentioning
confidence: 99%
“…Every-day short-term haemodialysis (6 times weekly, 3h) for 12 months decreases left ventricle hypertrophy by 30%, as compared to conventional haemodialysis (3 times weekly, 4h) [24]. Clinical trial results show that night-time haemodialysis (3 times weekly, 6-8h) during the six-month period significantly reduces left ventricle hypertrophy compared to conventional haemodialysis (3 times weekly, 4h) [25].…”
Section: Aetiopathogenesis Of Left Ventricle Hypertrophymentioning
confidence: 96%
“…Well-timed risk factor detection and adequate therapy help regression of left ventricle hypertrophy in haemodialysis patients [22][23][24][25]. Results of large, well-controlled clinical trials stress that the management of anaemia and blood pressure control, the correction of metabolic disorders of calcium, phosphate, vitamin D and parathormone (parathyroid hormone), as well as the individualisation of treatment of haemodialysis as the most important factors in the successful management of left ventricle hypertrophy [22][23][24][25].…”
Section: Therapy Of Left Ventricular Hypertrophymentioning
confidence: 99%
“…These conditions are consequences not only of increasing uremic toxemia but also of fluid overload, malnutrition, insulin resistance, as well as of erythropoietin administration. Many authors suggest that cardiovascular abnormalities in patients with ESRD are extremely detrimental and lead to a considerable percentage of fatal outcomes …”
Section: Introductionmentioning
confidence: 99%
“…Many authors suggest that cardiovascular abnormalities in patients with ESRD are extremely detrimental and lead to a considerable percentage of fatal outcomes. [1][2][3] The most common clinical presentation of cardiac impairments in the course of ESRD is probably the left ventricle hypertrophy. 4,5 The recent reports, concerning dialyzed children, have revealed that systolic function of the left ventricle keeps intact only if there is no concomitant arterial hypertension, anemia, or heart failure.…”
Section: Introductionmentioning
confidence: 99%